Peningkatan Potensi Mahasiswa dalam Pendidikan Anak Usia Dini dan Generasi Muda Dusun Gondang - Natasya Z, Nazwa; Istiqomah, Wardah; Faqih, Muhammad; Defrianto, M. Donny; Putra, Royan Zanuar; Rochani, Titis Sobri; Maryati, Sri; Widyanto, Sadewa Yudhitya; Randhana, Destria; Supriatna, Salsabilla Feby; Muhajir, Mohamad (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Early childhood education is an important foundation in the formation of character and intelligence of the nation's next generation. This research aims to analyze the effectiveness of student empowerment programs in early childhood education assistance in Padukuhan Gondang, Donokerto Village, Turi District, Sleman Regency. The methods used in this research include interviews, participant observation, and documentation, focusing on three main programs: mentoring PAUD Cerdas Ceria, TPA Al-Hasanah, and tutoring for kindergarten and elementary school children. The results showed that the mentoring program succeeded in increasing children's enthusiasm and active participation in the learning process. The interactive and creative learning approach applied is able to encourage children's cognitive, social, and emotional development. The mentoring program at PAUD Cerdas Ceria succeeded in increasing interest in learning through various experimental activities and educational games. Activities at TPA Al- Hasanah contribute to strengthening religious understanding and character building, while the tutoring program helps improve children's academic achievement and self- confidence. This research concludes that student empowerment in early childhood education has a significant positive impact, not only on children's development but also on improving the quality of education in Gondang Padukuhan as a whole